THE EFFECT OF Eugenia polyantha EXTRACT ON LDL CHOLESTEROL - Siregar, Ratih Nur Indah (Majority, 2015)
Abstract Hypercholesterolemia is a disease of cholesterol metabolism disorder caused by the cholesterol levels in the blood is abnormal . Pharmacology treatment can give side effects when it is used in the long term so that the herbal medicine has been commonly used for treatment , such as bay leaves. Eugenia polyantha is the seasoning that is often used as ingredientfor cooking because its typical aroma and its fragrance. Eugenia polyantha has some benefits for the healthy like for treating diabetes mellitus, diarrhea, hypertension, gastritis and cholesterol. If the level bad cholesterol or LDL increasein the blood, it can be thickness and become constriction in artery. While this condition always occur, it can be coronary heart disease. WHO reported that coronary heart disease causes seven millions peoples died in the world and become the first position for the number of death in Indonesia. Keyword : coronary heart disease, Eugenia polyantha, hypercholesterolemia, LDL level Abstrak Hiperkolesterolemia adalah penyakit gangguan metabolismekolesterol yang disebabkan oleh kadar kolesterol dalam darah melebihi batas normal . Pengobatan secara farmakolgi dapat memberikan efek samping apabila digunakan dalam jangka panjang sehingga tanaman herbal mulai dimanfaatkan untuk pengobatan, seperti daun salam. Daun salam (Eugenia polyantha) merupakan bumbu masak yang sering digunakan sebagai bahan dalam masakan karena aromanya yang khas dan wangi. Daun salam memiliki banyak manfaat untuk kesehatan, seperti mengobati diabetes mellitus, diare, hipertensi, gastristis dan kolesterol. Kolesterol jahat atau disebut juga LDL apabila meningkat kadarnya dalam darah dapat menyebabkan terjadinya penebalan dan penyumbatan pada pembuluh darah. Apabila keadaan ini terjadi terus menerus dapat menimbulkan penyakit jantung koroner. WHO melaporkan bahwa penyakit jantung koroner menyebabkan tujuh juta orang meninggal di dunia dan menduduki tingkat pertama penyebab kematian di Indonesia. Kata kunci: Eugenia polyantha, hiperkolesterolemia,kadar LDL, penyakit jantung koroner